WET DEPOSITION QUALITY IN BANDUNG AREA AND IDENTIFICATION OF ITS POLLUTANT SOURCES - Yuniarti Hasan, Nia
Wet deposition is the scavenging process of pollutants, naturally transport to Earth’s surface with rain, snow or fog. The Monitoring of wet deposition in Indonesia has been carried out by EANET (East Asia Acid Deposition Network) on 5 (five) monitoring stations including in Bandung. Wet deposition quality research, especially the concentration of heavy metals in the Bandung area was needed because rainwater was an indicator of impact local and long-range transport emission natural and anthropogenic air pollutant in an urban area. Research of wet deposition quality in Bandung area were aimed at an analysis of characteristics and identification of its pollutant sources in Bandung area. This study analyzed historical secondary data of EANET in 2003–2015, and primary data from research results in the Bandung area in 2016–2017 at 4 (four) different locations in the Bandung area. The research can be used for air quality management consideration in the Bandung area.